Date fruit melanin is primarily based on (−)-epicatechin proanthocyanidin oligomers - Alam, Muneeba Zubair; Okonkwo, Clinton Emeka; Cachaneski-Lope, João P. [UNESP]; Graeff, Carlos F. O. [UNESP]; Batagin-Neto, Augusto [UNESP]; Tariq, Saeed; Varghese, Sabu; O’Connor, Matthew J.; Albadri, Abuzar E.; Webber, J. Beau W.; Tarique, Mohammed; Ayyash, Mutamed; et al. (Springer Nature, 2024)
Plant-based melanin seems to be abundant, but it did not receive scientific attention despite its importance in plant biology and medicinal applications, e.g. photoprotection, radical scavenging, antimicrobial properties, etc. Date fruit melanin (DM) has complex, graphene-like, polymeric structure that needs characterization to understand its molecular properties and potential applications. This study provides the first investigation of the possible molecular composition of DM. High performance size-exclusion chromatography (HPSEC) suggested that DM contains oligomeric structures (569–3236 Da) and transmission electron microscopy (TEM) showed agglomeration of these structures in granules of low total porosity (10–1000 Å). Nuclear magnetic resonance (NMR) spectroscopy provided evidence for the presence of oligomeric proanthocyanidins and electron paramagnetic resonance (EPR) spectroscopy revealed a g-factor in the range 2.0034–2.005. Density functional theory (DFT) calculations suggested that the EPR signals can be associated with oligomeric proanthocyanidin structures having 4 and above molecular units of (−)-epicatechin. The discovery of edible melanin in date fruits and its characterization are expected to open a new area of research on its significance to nutritional and sensory characteristics of plant-based foods.
Keywords: (−)-Epicatechin; Date fruit; Melanin; Phoenix dactyliferaL; Proanthocyanidins